2018
DOI: 10.1007/s40565-018-0398-0
|View full text |Cite
|
Sign up to set email alerts
|

Short-term local prediction of wind speed and wind power based on singular spectrum analysis and locality-sensitive hashing

Abstract: With the growing penetration of wind power in power systems, more accurate prediction of wind speed and wind power is required for real-time scheduling and operation. In this paper, a novel forecast model for shortterm prediction of wind speed and wind power is proposed, which is based on singular spectrum analysis (SSA) and locality-sensitive hashing (LSH). To deal with the impact of high volatility of the original time series, SSA is applied to decompose it into two components: the mean trend, which represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…In Fig. 4d, only four points (2,8,64,67) in the predicted segment do not meet the prediction requirements. It can be observed that the method of this paper is still the most reliable.…”
Section: Results Comparison For Different Algorithmsmentioning
confidence: 98%
See 3 more Smart Citations
“…In Fig. 4d, only four points (2,8,64,67) in the predicted segment do not meet the prediction requirements. It can be observed that the method of this paper is still the most reliable.…”
Section: Results Comparison For Different Algorithmsmentioning
confidence: 98%
“…In Fig. 4b, only four points (1,2,64,67) in the predicted segment do not meet the prediction requirements. In Fig.…”
Section: Results Comparison For Different Algorithmsmentioning
confidence: 99%
See 2 more Smart Citations
“…That is, for any distinct trajectory pattern, when there are more than 150 patients in the cohort sharing this pattern, the prediction for new patients who also have this trajectory pattern will be accurate. Since patient numbers in EMR data can easily reach into the million range, it is promising to build a large database of trajectory patterns in existing patients and use locality sensitive hashing (28)(29)(30)(31) and approximate nearest neighbor query techniques (32,33) to predict disease progressions in new patients. clusters color-coded by kidney functions (blue: good, red: impaired); clusters enriched with encounters of patients of high-or low-risk APOL1 genotypes (middle and right, correspondingly).…”
Section: Prediction Of Chronic Disease Progressionmentioning
confidence: 99%